Sosialiasi Pencegahan Hipertensi Pada Remaja di Sekolah Melalui Gerakan Jaga Jantung Dengan Gerak Aktif Senam Jantung Sehat - Yuningsih, Aneng; Suprapti, Betty; Kurnia, Anih; Gustiani, Mia Ruhmiati; Asparina, Arina; Ismawi, Ade Sayid; Purnama Sari, N.Jihan Audiya (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Abstract Hypertension is a chronic condition with a high prevalence, increasing the risk of cardiovascular diseases such as stroke, heart attack, and kidney failure. Recent data suggest that hypertension affects not only adults but also adolescents, with a rising prevalence. Major risk factors include an unhealthy lifestyle, obesity, genetic predisposition, and lack of physical activity. Preventive efforts are essential to increase awareness among adolescents about maintaining heart health through physical activity. This community service program aimed to enhance adolescents' understanding of hypertension risks and prevention through the "Heart Care Movement" with Healthy Heart Exercise. Conducted at SMAN 7 Tasikmalaya, the program involved 86 grade XII students. Methods included interactive education using leaflets and the implementation of Healthy Heart Exercise led by instructors from the Bachelor of Nursing program at Universitas Bakti Tunas Husada. Evaluations involved pre-test and post-test knowledge assessments and monitoring participants' heart rates. Results indicated a significant improvement in students' knowledge about hypertension and the benefits of physical activity. The average knowledge score increased from 59.77 in the pre-test to 83.02 in the post-test. Active participation in education and exercise sessions demonstrated strong enthusiasm for the program. Supported by the Community-Based Participatory Research (CBPR) model, which actively engaged the school, this initiative proved effective in raising awareness. Integrating such programs into routine school activities could foster a culture of healthy living from an early age and reduce future hypertension risks. Keywords: hypertension, adolescents, prevention, healthy heart exercise, community service.